2015
DOI: 10.1017/s0007114514003717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a high-fat diet on the hepatic expression of nuclear receptors and their target genes: relevance to drug disposition

Abstract: More than 1·4 billion individuals are overweight or obese worldwide. While complications often require therapeutic intervention, data regarding the impact of obesity on drug disposition are scarce. As the influence of diet-induced obesity on drug transport and metabolic pathways is currently unclear, the objective of the present study was to investigate the effect of high fat feeding for 13 weeks in female Sprague -Dawley rats on the hepatic expression of the nuclear receptors pregnane X receptor (PXR), consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 54 publications
(58 reference statements)
2
25
0
Order By: Relevance
“…In the context of previous reports, results in mouse models of NAFLD have been heterogeneous with some demonstrating decreased (Yoshinari et al, 2006;Ghose et al, 2011;Wahlang et al, 2014) or induced (Fisher et al, 2008;Spruiell et al, 2014) expression of Cyp3a11. Similarly, rat models of hepatic steatosis are conflicting, with some reporting decreased Cyp3a expression (Leclercq et al, 1998) and others showing higher levels (Ghoneim et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of previous reports, results in mouse models of NAFLD have been heterogeneous with some demonstrating decreased (Yoshinari et al, 2006;Ghose et al, 2011;Wahlang et al, 2014) or induced (Fisher et al, 2008;Spruiell et al, 2014) expression of Cyp3a11. Similarly, rat models of hepatic steatosis are conflicting, with some reporting decreased Cyp3a expression (Leclercq et al, 1998) and others showing higher levels (Ghoneim et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Second, Kim et al also showed for comparison, that along with FXR, PXR acetylation levels are also elevated in response to HFD-induced obesity in mouse liver, suggesting that obesity may represent the physiological relevance of PXR acetylation. In this context, HFD in rodents also increases PXR levels, perhaps highlighting the significance for overall PXR acetylation effects in obesity [86]. In fact, it is becoming clear that nutrient excess conditions promote global hepatic acetylation of metabolic regulators in general, including NRs, for metabolic adaptation [8793].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is becoming clear that nutrient excess conditions promote global hepatic acetylation of metabolic regulators in general, including NRs, for metabolic adaptation [8793]. A counter argument is that this acetylation state/level could simply reflect an adaptation to increased expression of PXR in HFD- fed rodents [86, 94, 95]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In LPM from HFD-fed mice, no significant change in ABCA1 expression was observed, despite the increased ubiquitination of ABCA1. This is likely to be because of the net outcome of transcriptional induction of ABCA1 mRNA 30,31 and lysosomal degradation of ubiquitinated csABCA1.…”
Section: Decreased Interaction Of Abca1 With Lxrβ and Increased Ubiqumentioning
confidence: 99%